Comparison of transrectal and transabdominal transducers for use in fast localized abdominal sonography of horses presenting with colic - Haardt, Hanna; Romero, Alfredo E.; Boysen, Søren R.; Tan, Jean-Yin (Frontiers in Veterinary Science, 2024)
Abdominal ultrasonography is valuable in the diagnosis of equine colic. Fast localized abdominal sonography of horses (FLASH) enables practitioners with limited experience to perform ultrasonography in emergency settings. However, many practitioners only possess rectal format linear array transducers (RFLT). The hypotheses are: (a) A low frequency curvilinear transducer (LFCT) and RFLT will detect free abdominal fluid and abnormal small intestinal loops with similar frequency during FLASH, and (b) there will be a difference between the transducers for detection of gastric abnormalities and nephrosplenic entrapment. The objective is to compare transcutaneous abdominal ultrasonographic detection of abnormalities in horses presenting with colic using a LFCT and RFLT. Twenty-four horses requiring FLASH for investigation of colic were enrolled. Horses that were too painful to undergo transcutaneous abdominal ultrasonographic examination were excluded. A single investigator performed FLASH on all horses using a RFLT, while one of three other clinicians simultaneously performed FLASH using a LFCT. Comparison of abnormal findings between the two transducers was performed using Chi square, Fisher's exact or Wilcoxon tests. The incidence of identification of abnormal findings was similar between the two transducers for all comparisons except the visibility of the left kidney and stomach (kidney LFCT 81.25% vs RFLT 22.92%, stomach LFCT 87.5% vs. RFLT 62.5%).While there are limitations to using a RFLT to identify nephrosplenic entrapment of the colon and detection of the stomach, it reliably detects other common abnormalities, including peritoneal effusion, lesions of the small intestine, and changes to the wall of the large colon and cecum.